Clock Genes Disruption in the Intensive Care Unit. (December 2020) - Diaz, Elena; Diaz, Irene; del Busto, Cecilia; Escudero, Dolores; Pérez, Silvia
Background: Intensive care unit (ICU) environment disrupts the circadian rhythms due to environmental and other nonphotic synchronizers. The main purpose of this article is to establish whether critically patients have desynchronization at the molecular level after 1 week of stay in the ICU. Methods: The rhythm of Clock, Bmal1, Cry1, and Per2 genes in neuro-ICU patients (n = 11) on the first day after admission in the unit (1 day) and 1 week later (1 week) was studied, 4 time points throughout the day, at 6, 12, 18, and 24 hours. Human whole blood samples were obtained from neuro-ICU patients. The total RNA was isolated and each sample was reverse transcribed to complementary DNA and quantitative polymerase chain reaction (PCRq) was performed. The possible rhythm was studied using Fourier Series. Results: After 1 week, the clock gene rhythmicity completely disappeared. Messenger RNA (mRNA) expression for the 4 clock genes was shown rhythmicity at the first day after admission in the ICU. Circadian rhythmicity for none of them was observed but rather, ultradian rhythmicity was found. The expression of Clock, Bmal1, and Per2 mRNA after 1 week was similar in the 4-time point studies without significant fluctuation among the 4 time points analyzed. Discussion: Rhythmic mRNA expression is present at the first day after admission in the ICU. However, ICU stay during 1 week affects the molecular machinery of the biological clock generating chronodisruption. Circadian disruption is associated with the risk of several pathologies, thus, it seems to be clear that ICU stay in constant conditions could adversely affect patient evolution and probably, circadian resynchronization restoring clock gene expression could lead to a better clinical evolution of the patient. Conclusions: Clock genes disruption is observed in neuro-ICU patients. Light therapy as well as melatonin treatment could reduce the impact of ICU stay period in biological clock, thereby improving patients' recovery.